The effect of education on teenage fertility: Causal evidence for Argentina - María Laura Alzúa; Cecilia Velázquez (IZA Journal of Development and Migration, 2017)
This is the first study exploring the causal effect of education on teenage fertility in Argentina. We exploit an exogenous variation in education from the staggered implementation of the 1993 reform, which increased compulsory schooling from 7 to 10 years. We find a negative overall impact of education on teenage fertility rates, which operates through two complementing channels: a human capital effect (one additional year of schooling causes a decline of 30 births per 1000 girls) and a weaker 'incapacitation' effect (a rise of one percentage point in enrollment rate reduces 3 births per 1000 girls).
Keywords: I25; I28; J13; J16; 330; Teenage fertility; Education; Instrumental variables; Compulsory schooling laws; Latin America and the Caribbean; Argentina